Intervention Adherence in REHAB‐HF: Predictors and Relationship With Physical Function, Quality of Life, and Clinical Events - M. Benjamin Nelson; Olivia N. Gilbert; Pamela W. Duncan; Dalane W. Kitzman; Gordon R. Reeves; David J. Whellan; Robert J. Mentz; Haiying Chen; Leigh Ann Hewston; Karen M. Taylor; Amy M. Pastva (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background The REHAB‐HF (Rehabilitation Therapy in Older Acute Heart Failure Patients) trial showed that a novel, early, transitional, tailored, progressive, multidomain physical rehabilitation intervention improved physical function and quality of life in older, frail patients hospitalized for acute decompensated heart failure. This analysis examined the relationship between intervention adherence and outcomes. Methods and Results Adherence was defined as percent of sessions attended and percent of sessions attended adjusted for missed sessions for medical reasons. Baseline characteristics were examined to identify predictors of session attendance. Associations of session attendance with change in physical function (Short Physical Performance Battery [primary outcome], 6‐minute walk distance, quality of life [Kansas City Cardiomyopathy Questionnaire], depression, and clinical events [landmarked postintervention]) were examined in multivariate analyses. Adherence was 67%±34%, and adherence adjusted for missed sessions for medical reasons was 78%±34%. Independent predictors of higher session attendance were the following: nonsmoking, absence of myocardial infarction history and depression, and higher baseline Short Physical Performance Battery. After adjustment for predictors, adherence was significantly associated with larger increases in Short Physical Performance Battery (parameter estimate: β=0.06[0.03–0.10], P=0.001), 6‐minute walk distance (β=1.8[0.2–3.5], P=0.032), and Kansas City Cardiomyopathy Questionnaire score (β=0.62[0.26–0.98], P=0.001), and reduction in depression (β=−0.08[−0.12 to 0.04], P<0.001). Additionally, higher adherence was significantly associated with reduced 6‐month all‐cause rehospitalization (rate ratio: 0.97 [0.95–0.99], P=0.020), combined all‐cause rehospitalization and death (0.97 [0.95–0.99], P=0.017), and all‐cause rehospitalization days (0.96 [0.94–0.99], P=0.004) postintervention. Conclusions In older, frail patients with acute decompensated heart failure, higher adherence was significantly associated with improved patient‐centered and clinical event outcomes. These data support the efficacy of the comprehensive adherence plan and the subsequent intervention‐related benefits observed in REHAB‐HF. Registration URL: https://clinicaltrials.gov/; Unique identifier: NCT02196038.